2018
DOI: 10.1111/cdev.13136
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative and Differential Effects of Early Child Care and Middle Childhood Out‐of‐School Time on Adolescent Functioning

Abstract: Effects associated with early child care and out-of-school time (OST) during middle childhood were examined in a large sample of U.S. adolescents (N = 958). Both higher quality early child care AND more epochs of organized activities (afterschool programs and extracurricular activities) during middle childhood were linked to higher academic achievement at age 15. Differential associations were found in the behavioral domain. Higher quality early child care was associated with fewer externalizing problems, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Maternal education in years was measured at the 1-month home visit. These indicators are reliable measures and have been used in several studies with the NICHD SECCYD data (Vandell et al, 2016;Vandell, Lee, Whitaker, & Pierce, 2020). Descriptive and correlational statistics of continuous covariates are provided in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…Maternal education in years was measured at the 1-month home visit. These indicators are reliable measures and have been used in several studies with the NICHD SECCYD data (Vandell et al, 2016;Vandell, Lee, Whitaker, & Pierce, 2020). Descriptive and correlational statistics of continuous covariates are provided in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…The mean hours per week across the 13 epochs was highly correlated with the proportion of epochs ( r = .60). A proportion of epochs in organized activities was used in the primary analyses because it was less skewed than mean hours per week and had been previously linked to child developmental outcomes during middle childhood (NICHD Early Childcare Research Network, 2004; Vandell et al, 2020a).…”
Section: Methodsmentioning
confidence: 99%
“…In that paper, higher-quality early childcare AND more epochs of organized activities during middle childhood were both linked to higher academic achievement at age 15 years, consistent with Zigler and Berman's (1983) proposition that cumulative experiences in early childhood and middle childhood may result in larger, sustained academic gains. In addition, Vandell et al (2020a) found differential associations in the behavioral domain at age 15. ECE hours was related to less impulse control at age 15, whereas organized activities during middle childhood were not related to impulse control at that age.…”
Section: After-school Organized Activities and Later Problem Behaviorsmentioning
confidence: 99%
“…Empirical studies provide support for the benefits of extracurricular involvement on multiple child outcomes during the school‐age and adolescent years. Higher levels of extracurricular involvement initiated at school‐age have been associated with subsequent socioemotional and academic adjustment during the school‐age years (Aumètre & Poulin, 2018; Denault & Déry, 2015; Oberle, Ji, Magee, et al, 2019) and in adolescence (Metsäpelto & Pulkkinen, 2012; Neely & Vaquera, 2017; Oberle, Ji, Guhn, Schonert‐Reichl, & Gadermann, 2019; Vandell, Lee, Whitaker, & Pierce, 2018). These results also have been evident for adolescents from low‐income households.…”
Section: Introductionmentioning
confidence: 99%